Pendekatan Caleg Terpilih Pada Suku Anak Dalam (SAD) di Desa Bukit Suban Pada Pileg 2024 (Sebuah Penelitian Kualitatif Untuk Mengetahui Pendekatan Caleg di Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun) - Joko Setyoko; Ronal Dison (Universitas Muara Bungo, 2024)
This research aims to understand the approach taken by elected legislative candidates toward the Indigenous Anak Dalam (SAD) community in Bukit Suban Village, Air Hitam District, Sarolangun Regency. The background of this study is based on the approach of legislative candidates in addressing the SAD community, many of whom are illiterate and have a mindset that has not been touched by schooling or the education process, making it difficult for them to communicate with the surrounding society. Legislative candidates must truly guide and engage with them so that they are willing to connect with the candidates, with the hope of gaining votes as expected. In this study, the author uses a qualitative descriptive analysis method. The informants are members of the SAD community and legislative candidates who are competing in the 2024 legislative elections. To collect data, the author conducted literature studies, field studies, and documentation studies. The results of this research show that the approach to the SAD community as voters must be different from the approach to the general population. Therefore, the legislative candidates use traditional, behavioral, and rational approaches. The solution is to be patient and persistent when approaching the SAD community and to provide them with rights and duties as Indonesian citizens, while respecting their customs and traditions.